Structural characterization of the (MeSH) 4 potential energy surface (2013)
A random walk on the PES for (MeSH)4 clusters produced 50 structural isomers held together by hydrogenbonding networks according to calculations performed at the B3LYP/6–311++G** and MP2/6–311++G** levels -- The geometric motifs observed are somewhat similar to those encountered for the methanol tetramer, but the interactions responsible for cluster stabilization are quite different in origin -- Cluster stabilization is not related to the number of hydrogen bonds -- Two distinct, well-defined types of hydrogen bonds scattered over a wide range of distances are predicted